STUDI LITERATUR: PROGRAM PEMBERIAN MAKAN DI SEKOLAH DAN HUBUNGANNYA DENGAN STATUS GIZI - Ulfah, Syafrina; Handayani, Fitri (Jurnal Penelitian Kesmasy, 2025)
Malnutrition in school-aged children continues to be a public health issue in Indonesia. The Free Nutritious Meal Program (MBG), established in Indonesia, has the capacity to mitigate malnutrition among school-aged children. This literature review examines the impact of school feeding programs on children's nutritional status, referencing prior research. The review synthesizes evidence from studies conducted in countries including China, Ethiopia, Ghana, and the United States. Findings suggested that school feeding programs can improve the nutritional status of school-aged children, particularly in resource-limited areas. These programs have been shown to impact health outcomes positively (such as weight, height, and BMI) and contribute to overall health improvement. Targeting vulnerable children is crucial for the success of school feeding programs. Program design must prioritize food diversity, adequate nutritional content, and food safety to ensure effectiveness. Continuous monitoring and further research are essential to eval__uate and enhance the long-term impact of these interventions.